Exploring the Use of Structure and Polymer Incorporation to Tune Silver Ion Release and Antibacterial Activity of Silver Coordination Polymers. Issue 30 (10th August 2018) - Young, Rosemary J.; Begg, Stephanie L.; Coghlan, Campbell J.; McDevitt, Christopher A.; Sumby, Christopher J.
Abstract : The use of silver as an antibacterial agent has seen renewed interest as a result of its ability to combat a broad range of bacterial species, including those resistant to multiple classes of antibiotics. Silver coordination polymers (CPs) provide the opportunity to control the release of silver ions, thus avoiding unwanted side effects and toxicity; however, the parameters that tune release remain poorly understood. Here, four silver CPs, namely [Ag2 (Me4 bpz )] as both four‐ and eightfold interpenetrated forms, and [Ag(dpzm )(ClO4 )] in its open 3D and close‐packed 2D forms, were used to probe the role of structure in the release of silver ions. Release was measured by inductively‐coupled plasma mass spectrometry (ICP‐MS) and shown to be more marked for the charged networks, [Ag(dpzm )(ClO4 )] (complete dissolution). Incorporation of the silver CPs into inert polymer matrices, polyethylene and polycaprolactone, to provide surface coatings was also investigated, and shown to significantly retard silver ion release. The antibacterial activities of all materials as their polymer composites were analysed by disk diffusion and bacterial growth assays. All CPs showed antibacterial activity, with the Gram‐positive Staphylococcus aureus exhibiting greater sensitivity to silver than the Gram‐negative Escherichia coli . Metal–ligand bond strength and anion availability were found to influence silver release into aqueous solution but this did not always correlate with the in vitro antibacterial activity. Abstract : Although the antibacterial activity of silver coordination polymers continues to attract interest, the parameters that modulate release remain poorly understood. Herein, structural features, such as bonding and topology, were used to modulate the release of silver and the antibacterial activities of four silver coordination polymers and their polymer composites.